(3GdeMUhd aj CUhd Gdabgs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQafG HGdESdGe CeG HYO agPG cJGH LeYfG ajg GdOdGFd GdeYJHQI GdaUd GdChd ai JaSjQ CUhd Gdabg GdeQcH s
(3BNQgG (B:s
(3hGYde CfG EfeG LeYfG gPg GdhLhg dCf CcKQ efGXQGJ Cgd GdReGf ai Gdabg hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjO GdChdjf hGdBNQjf eMeO hBdg CLeYjf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs